Single‐Molecule Ex Situ Atomic Force Microscopy Allows Detection of Individual Antibody–Antigen Interactions on a Semiconductor Chip Surface. Issue 2 (5th February 2021) - Lu, Ming-Pei; Weng, Ying-Ya; Yang, Yuh-Shyong
Abstract : Single‐Molecule Detection An ex‐situ atomic force microscopy (AFM)–molecule chip technique allows the ex‐situ AFM analysis detection of antibody–antigen interactions at the single‐molecule level. This approach is significantly superior to conventional in‐situ AFM analysis detection in terms of its practicality, flexibility, and versatility. More details can be found in article number 2000035 by Ming‐Pei Lu and co‐workers.